Development and Application of Infrared Video Intelligent Diagnosis Device for Substation Equipment Based on Edge Calculation. Issue 1 (1st August 2022) - Liu, Guangwei; Mu, Ka; Liu, Boyan; Ma, Xinsheng; Hao, Zhen; Ma, Jixian
Abstract: In recent years, infrared detection technology is widely used in the field of state detection of power equipment. It can timely and effectively find equipment defects and avoid the further development of equipment defects. However, the conventional manual inspection has some problems, such as heavy workload, long time-consuming and low efficiency. Based on the research of infrared image intelligent detection technology of substation equipment based on deep learning algorithm and digital image lossless compression technology, a set of infrared video intelligent diagnosis device of substation equipment based on edge calculation is developed and applied in practice. The device realizes local real-time rapid processing and timely diagnosis of equipment defects, and the accuracy of defect identification is about 94.44%, which greatly improves the safe and stable operation level and power supply reliability of substation equipment.